The medial femoral condyle free corticoperiosteal flap versus traditional bone graft for treatment of nonunions of long bones: a retrospective comparative cohort study. (December 2019) - Ciclamini, Davide; Tos, Pierluigi; Guzzini, Matteo; Soldati, Alessandra; Crosio, Alessandro; Battiston, Bruno
Abstract: Fracture healing is a complex process and many factors change the local biology of the fracture and reduce the physiologic repair process. Since 1991 the free vascularised corticoperiosteal graft has been proposed to treat nonunions. In this study we compare the healing rate and the healing time of the free vascularised corticoperiosteal graft harvested from medial femoral condyle versus the traditional cancellous bone graft from the iliac crest combined with other biologic or pharmacologic factors. We performed a retrospective cohort study. The main measures of outcomes were the rate of bone union and the mean healing time from surgery. The authors performed 10 free vascularised corticoperiosteal grafts in the cohort A and 10 patients received traditional cancellous bone graft plus other biologic or pharmacologic treatment in the same period in the cohort B. The mean follow up in cohort A was 18.6 months with a healing rate of 100% (10/10). In cohort B the mean follow up was 22.5 month with a healing rate of 90%. The mean time to obtain union (healing time) in the group that was treated with the free flap procedure was significantly shorter, 3.2 months versus a mean time of 8.8 months in the other group. Some studies describe a high healing rate of recalcitrant nonunions with treatments different from vascularized bone flaps: it is difficult to compare the results of vascularized bone transfers with the results of other case series. Our groups are very homogeneous even if it is difficult to define correct inclusion criteria because there is still no agreement about what is defined a recalcitrant or difficult nonunion, and the number of trials of previous surgery before to perform a vascularized free flap. Even if our study cohort is small, we have demonstrated that the MFCCF generally seems to give a better healing chance with a shorter healing time compared to other treatments.